2018
DOI: 10.1111/jtxs.12379
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gellan gum on functional properties of low‐fat chicken meat batters

Abstract: The effects of substituting pork back‐fat with addition of gellan gum and water on gel characteristics, rheological property, water mobility, and distribution of chicken meat batters were studied. The addition of gellan gum significantly affected the cooking yield, color, texture, and rheological property of chicken meat batters (p < .05). The cooking yield and textural properties were not significantly different (p > .05) when gellan gum was added with 0, 0.2, and 0.4%. When the level of gellan gum reached 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 54 publications
2
16
0
Order By: Relevance
“…This may be related to thickening or gelatinization behavior of the pre‐emulsified oil at high temperature during the steaming (heat treatment). These results were also found in a report, wherein gellan gum and water were added in chicken meat batters to reduce the pork back fat (Li et al, ). Based on the above data, it can be seen that steamed reduced‐fat fillings (33.3 and 66.7% replacement, respectively) showed similar texture quality with control filling.…”
Section: Resultssupporting
confidence: 77%
“…This may be related to thickening or gelatinization behavior of the pre‐emulsified oil at high temperature during the steaming (heat treatment). These results were also found in a report, wherein gellan gum and water were added in chicken meat batters to reduce the pork back fat (Li et al, ). Based on the above data, it can be seen that steamed reduced‐fat fillings (33.3 and 66.7% replacement, respectively) showed similar texture quality with control filling.…”
Section: Resultssupporting
confidence: 77%
“…However, NaCl plays an important role in the textural properties, water‐ and fat‐holding capacity, flavour and shelf life of emulsified meat products by improving the functional properties of meat proteins and inhibiting the growth of microorganisms (Kang et al ., 2019). Some studies have reported that the reduced NaCl content declines the quality of emulsified meat products (Li et al ., 2019; Kang et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were also observed by when chicken batters gels were treated with high pressure (0.1-400 Mpa). Previously, researchers have confirmed that polysaccharides can improve the WHC of meat products (Kang et al, 2020;Li et al, 2019). ASK gum with better water binding capacity can disperse in the interstitial spaces of the protein network to generate and improve the WHC of gels.…”
Section: Whcmentioning
confidence: 96%